Risks and Surgical Outcomes of Planned Re-Laparotomy for Secondary Peritonitis - Puddifoot W. Salgado; Fulgencio R. Mendoza (Academic Journal of Clinicians, 2025)
Intra-abdominal sepsis and severe secondary peritonitis remain among the most common pathologies and those with the greatest controversy in management. The therapeutic success in the management of this pathology translates into a decrease in mortalities and morbidities. This original study looks at the risks and effects of planned re-laparotomy for secondary peritonitis at Hospital Angeles Tijuana from 2020 to 2024. A total of 78 patients, 47 men and 31 women, were included. All of them got secondary peritonitis after having laparotomies and other procedures on their stomachs. The study's goal was to find out how many people became sick or died after this surgery. Patients had a full preoperative evaluation, and their medical histories were well recorded. We kept track of the results over a 30-day period and grouped the postoperative problems by how bad they were. The results showed a lot of problems, such as infections, organ failure, and protracted hospital admissions. The overall death rate was very high, which shows how hard it is to treat secondary peritonitis. This study shows how important it is to do surgery on time and how many different factors can affect the risks for patients who have to have re-laparotomy. The results show that better preoperative evaluation and postoperative treatment could lower the number of deaths and illnesses. The study gives us useful information on how to treat secondary peritonitis, and also stresses the need for more research to find the best ways to help these patients.